Pemaafan pada Mahasiswa Bangka Belitung dan Jawa Tengah Ditinjau dari Kecerdasan Emosi dan Asal Daerah - Aisya, Putri; Rizkyani, Virly Indah; Nabillah, Shafanissa; Akhnaf, Ardhito Faza; Nashori, Fuad (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Nowadays, students often face interpersonal conflicts caused by conflicting behaviors such as differences of opinion, interests or conflicts between individuals. Some previous studies have shown that the way to deal with a conflict is to forgive the person. This study aims to find out the relationship between emotional intelligence and forgiveness in Bangka Belitung and Central Java students. A total of 109 students studied in Bangka Belitung and Central Java obtained through purposive sampling techniques. The measurement used in this study is a short-form trait emotional intelligence questionnaire (TEIQUE-SF) scale with an alpha cronbach coefficient of 0.981 and a forgiveness scale of 0.935. The results of the study showed a positive relationship between emotional intelligence and proven forgiveness of a significant (2-tailed) result of 0.048 (p 0.05). However, the results of the analysis also showed that there was no difference in the level of emotional intelligence and forgiveness among students studying in Bangka Belitung and Central Java. The results also showed no difference in forgiveness between students from Central Java Province and Bangka Belitung Province with a probability value of forgiveness variable (sig.) of 0.467 (p .05)